2021
DOI: 10.3390/ani11040964
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms at Myostatin Gene (MSTN) and the Associations with Sport Performances in Anglo-Arabian Racehorses

Abstract: One hundred and eighty Anglo-Arabian horses running 1239 races were sampled for the present study. DNA was extracted from the blood and myostatin gene, MSTN, was genotyped. Moreover, prizes won and places were achieved for the 1239 races to perform association analyses between the different genotypes and sport traits. Two SNPs already reported in previous studies regarding the Thoroughbred breed, rs69472472 and rs397152648, were revealed as polymorphic. The linkage disequilibrium analysis investigating the hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Many scientists reported that this variant is associated with the racing performance and muscle development among different breeds of horses. Preceding studies showed a significant difference in genotypic and allelic frequencies associated with racing performance in thoroughbred and Anglo-Arabian breeds horse population (3,10).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many scientists reported that this variant is associated with the racing performance and muscle development among different breeds of horses. Preceding studies showed a significant difference in genotypic and allelic frequencies associated with racing performance in thoroughbred and Anglo-Arabian breeds horse population (3,10).…”
Section: Discussionmentioning
confidence: 99%
“…Function of this protein is to restrict the development and growth of muscle fibers. In recent studies, researchers found that the MSTN is linked to racing performance, growth of skeletal muscle and carcass quality traits in different species including livestock animals, dogs, and horses (4) Moreover, the Myostatin gene is a major determinant of racing performance because it also influences the proportion of fast twitch and slow twitch muscle fibers in horses (3,5,6).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arabians are also highly appreciated as racehorses and earn considerable rewards throughout their gallop racing careers [ 4 , 8 ]. In addition, the Arabian horse breed is recognized as the leading breed in endurance competitions [ 9 ], but there was no evidence that this breed was genetically superior to other racehorse breeds [ 10 ]. Machmoum et al [ 11 ] argued that the genetic diversity of the Arabian horse breed decreases near the risk threshold, which should be considered in breeding studies.…”
Section: Introductionmentioning
confidence: 99%